Short-term clinical effectiveness and safety analysis of polidocanol foam sclerotherapy in the treatment of 62 exceptional patients with hemorrhoids - Zeng Xiangsheng; Ye Hui; Yu Jie; Li Haoping; Xiang Shang; Liu Zhong; Zeng Tao (结直肠肛门外科)
[Objectives] To analyze the short-term clinical effectiveness and safety of polidocanol foam sclerotherapy in the treatment of exceptional patients with hemorrhoids. [Methods] A retrospective analysis was conducted on the clinical data of 62 exceptional patients with hemorrhoids treated with polidocanol foam sclerotherapy at Jingzhou Hospital Affiliated to Yangtze University from August 2021 to November 2023. These patients included those with chronic renal failure in uremic stage, advanced liver cancer, advanced lung cancer, unstable leukemia, lymphoma during chemotherapy, severe anemia refusing blood transfusion, coagulation dysfunction, and severe cardiovascular and cerebrovascular diseases with contraindications for anticoagulation drug withdrawal. The operative time, pre- and post-operative (1-month) Short Health Scale for hemorrhoidal disease (SHSHD) score, Wexner constipation score, clinical effectiveness (evaluated at 1 week and 1 month post-surgery), anal pain on postoperative day 1, adverse reactions, and patient satisfaction rate (evaluated at 1 month post-surgery) were analyzed. Some patients received a second treatment within 1 month after the first treatment, and the time points for post-operative evaluation were calculated from the time of first treatment. [Results] Among the 62 patients, the mean operative time was (12.1±2.3) minutes. The SHSHD score and Wexner constipation score were significantly lower at 1 month post-surgery compared to pre-surgery (P<0.05). The overall effective rate was 93.5% (58/62) at 1 week post-surgery and 96.8% (60/62) at 1 month post-surgery. On postoperative day 1, 16 patients with pre-existing anal pain reported improvement, while 17 of the 46 patients without pre-existing anal pain reported mild anal pain. No allergic reactions, fever, local infections, or abscess formation were observed in any patients. The patient satisfaction rate was 95.2% (59/62) at 1 month post-surgery. [Conclusion] Polidocanol foam sclerotherapy can be considered as a treatment option for exceptional patients with hemorrhoids who have high surgical and anesthesia risks, demonstrating good short-term clinical effectiveness and safety.